Janu Sirsasana: Konsep dan Manfaatnya Bagi Kesehatan Diri - I Gusti Made Widya Sena (Jurnal Yoga dan Kesehatan, 2019)
Yoga is union. Unification between the individual soul and the universal soul. Unite the body with mind and mind with the soul. Knowledge of yoga can help to maintain the purity of soul by doing movements or poses on his body. Sirsasana pose is one of the poses that can be used for many people whose work is mostly spent behind a desk or computer. By working behind a desk or computer, someone will spend hours and sitting and keeping his body awake. In addition to maintaining the natural functions of the pelvis and lower back, the sitting position in yoga also has to do with training at a more advanced level. The word “asana” can actually be interpreted literally as sitting. And from a certain perspective, all asana exercises can be seen as a methodical way to free the spine, legs and breathing, so that yoga practitioners can be in a sitting position for a long time.